2008
DOI: 10.1105/tpc.107.054007
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the Plastidial α-Glucan Phosphorylase Gene in Rice Affects the Synthesis and Structure of Starch in the Endosperm

Abstract: Plastidial phosphorylase (Pho1) accounts for ;96% of the total phosphorylase activity in developing rice (Oryza sativa) seeds.From mutant stocks induced by N-methyl-N-nitrosourea treatment, we identified plants with mutations in the Pho1 gene that are deficient in Pho1. Strikingly, the size of mature seeds and the starch content in these mutants showed considerable variation, ranging from shrunken to pseudonormal. The loss of Pho1 caused smaller starch granules to accumulate and modified the amylopectin struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
219
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(230 citation statements)
references
References 65 publications
7
219
2
2
Order By: Relevance
“…A mandatory role of both isoamylase and pullanase types of debranching enzyme for amylopectin biosynthesis was clearly shown in maize endosperm and Arabidopsis leaves Streb et al, 2008). Mutation of the plastidial a-glucan phosphorylase gene affects the synthesis and fine structure of amylopectin in rice endosperm (Satoh et al, 2008). Therefore, the strong expression of PHO1 in barley may also be connected with starch synthesis.…”
Section: In the Developing Endosperm Starch Breakdown Occurs In The mentioning
confidence: 97%
“…A mandatory role of both isoamylase and pullanase types of debranching enzyme for amylopectin biosynthesis was clearly shown in maize endosperm and Arabidopsis leaves Streb et al, 2008). Mutation of the plastidial a-glucan phosphorylase gene affects the synthesis and fine structure of amylopectin in rice endosperm (Satoh et al, 2008). Therefore, the strong expression of PHO1 in barley may also be connected with starch synthesis.…”
Section: In the Developing Endosperm Starch Breakdown Occurs In The mentioning
confidence: 97%
“…However, we failed to detect SSIIIa in the granule-bound fraction in both TQ and TRS (data not shown). For Pho1, it has been reported that it produces short-chained MOS, and the resulting maltooligosaccharides (MOS) is able to prime amylose synthesis (Kitamura et al, 1982;Satoh et al, 2008). Pho1 exhibited a granule-bound fraction in TRS (Fig.…”
Section: Granule-bound Amylopectin Biosynthetic Enzymes Are An Importmentioning
confidence: 99%
“…Amylopectin is synthesized by the combined action of several isoforms, including starch synthases (SSs), starch branching synthases (SBEs), and debranching enzymes (DBEs; Nakamura, 2002;Davis et al, 2003;Tetlow, 2006). In addition, starch phosphorylase 1 (Pho1) also has been reported to play a role in starch synthesis, although its precise role remains elusive (Yu et al, 2001;Satoh et al, 2008).…”
mentioning
confidence: 99%
“…Another research suggested that the loss of Pho1 causes starch granules to turn to small in size and modified the amylopectin structure in rice by the Pho1 mutation [64].…”
Section: Differential Expression and Phosphorylation Between A-and B-mentioning
confidence: 99%